Tradisi Pesta Panen Masyarakat Petani di Desa Samaenre Kabupaten Pinrang - Abdul Rahman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to elaborate in depth on the tradition of the farming community in Samaenre Village, Pinrang Regency, which is called maddoa. This research applies qualitative research methods with a phenomenological approach. Data collection was carried out by directly observing the implementation of maddoa. The results of these observations were strengthened by conducting in-depth interviews with farmers. The data is then analyzed by comparing and juxtaposing field data with relevant research results. The research results show that maddoa is a sacred ritual that the community still maintains today. This sacredness is proven by the requirement to wear sarongs for maddoa participants and the prohibition of women who are menstruating from being involved in this activity. Maddoa activities reached their peak when people made a pilgrimage to the grave of Petta Pallipa Putee who is believed to be an ancestor in Samaenre Village. For the people of Samaenre Village, maddoa is a form of expression of gratitude to God for safety in carrying out activities to cultivate rice fields to obtain adequate harvests. This tradition is also used as a social space for the community to strengthen family ties and the spirit of mutual cooperation in carrying out all activities in this village. The results of this research further strengthen the position of farming communities to carry out the maddoa tradition in a sustainable manner. It is hoped that this research can make a positive contribution to character development and strengthening local culture among generation z.